2013
DOI: 10.5187/jast.2013.55.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Decreased Carcass Grade of Finishing Pigs due to Increasing Market Weight on Carcass Quality Traits and Physicochemical and Sensory Quality Characteristics of the Loin and Belly

Abstract: The present study was undertaken to investigate the effects of the decreased carcass grade due to overweight on meat quality traits of the loin and belly. Out of 500 carcasses from 85-to 150-kg market pigs, seven average-size 1 + A carcasses, seven 1Aand twelve 1B carcasses almost weighing the upper limits allowed for the A (95 kg) and B (99 kg) grades, respectively, and 12 1B carcasses weighing 100 kg or greater were selected for the present study. Marbling score was greater in the 1 + A grade than in any oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This is much greater than 21. 4 mm of BFT at the same live weight in the low-energy diet-fed high-lean pigs (Park et al ., 2009a), in which the retrospectively assessed optimum slaughter weight for superior carcass and meat quality is 128±5 kg on the criteria that the optimum BFT is 22±1 mm (Park, 2011; Park et al, 2013a; MAFRA, 2014) and that the BFT increases at a rate of 0.20 to 0.25 mm/kg live weight (Jeong et al ., 2010; Park and Lee, 2011; Park et al ., 2013b). If the same criteria are adopted for the present pigs endowed with a medium lean gain potential, the optimum slaughter weight is assessed to be 116±4 kg.…”
Section: Discussionmentioning
confidence: 99%
“…This is much greater than 21. 4 mm of BFT at the same live weight in the low-energy diet-fed high-lean pigs (Park et al ., 2009a), in which the retrospectively assessed optimum slaughter weight for superior carcass and meat quality is 128±5 kg on the criteria that the optimum BFT is 22±1 mm (Park, 2011; Park et al, 2013a; MAFRA, 2014) and that the BFT increases at a rate of 0.20 to 0.25 mm/kg live weight (Jeong et al ., 2010; Park and Lee, 2011; Park et al ., 2013b). If the same criteria are adopted for the present pigs endowed with a medium lean gain potential, the optimum slaughter weight is assessed to be 116±4 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Barrows have a higher belly yield, thicker belly and backfat, and higher total fat content in their carcasses than gilts [ 26 , 27 ]. Pigs with a fast growth rate and heavier slaughter weight also produce more belly portion and have higher fat content in the belly cuts compared with those with a slow growth rate and lighter slaughter weight [ 17 , 23 , 27 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…The slaughter weight (SW) of finishing pigs is a significant economic and technical factor that greatly affects pork quality as well as production efficiency and profitability of pig production [ 1 3 ]. Lee et al [ 4 ] and Park et al [ 5 7 ] have shown that backfat thickness (BFT), dressing percentage, and pork belly yield increased as the SW of finishing pigs in the range of 110–138 kg increased.…”
Section: Introductionmentioning
confidence: 99%